GENETIC ANALYSIS OF YIELD AND ITS ATTRIBUTES IN RICE (Oryza sativa L.) - CH. SREELAKSHMI* and P. RAMESH BABU (The Journal of Research ANGRAU, 2020)
The experiment (2014-16) was conducted to study the genetic parameters for yield and itscontributing traits revealed that number of unfilled grains/ panicle, 1000 grain weight and grain yieldrecorded high PCV and GCV values. High heritability with high GA as% of mean (genetic advance aspercent of mean) was observed for effective bearing tillers per plant, number of filled grains/panicle,number of unfilled grains per panicle, 1000 seed weight and grain yield indicating the involvement ofadditive gene action in the inheritance of the traits hence it is sufficient to follow simple selection. Alight on correlation studies revealed that positive direct effect of grain yield was observed with numberof ear bearing tillers per plant, number of filled grains/ panicle, harvest index, days taken for 50%flowering and days taken for maturity and selection may be effective based on these traits to isolatehigh yielding genotypes. Path coefficient analysis revealed that, days taken for maturity, number ofear bearing tillers/plant, number of filled grains/ panicle and harvest index had shown high positivedirect effect as well as positive association with grain yield. Hence, the above traits may be consideredas an important criterion in the rice improvement programme